Contemporary high performance computing : from petascale toward exascale - Vetter, Jeffrey S. (Chapman & Hall/CRC computational science series., 2013)
"Preface We are pleased to present you with this collection of material that captures a snapshot of the rich history of practice in Contemporary High Performance Computing. As evidenced in the chapters of this book, High Performance Computing continues to flourish, both in industry and research, both domestically and internationally. While much of the focus of HPC is on the hardware architectures, a significant ecosystem is responsible for this success. Why I edited this book My goal with this book has been to highlight significant systems and facilities in high performance computing. Early on, my main focus was proposed to be on the architectural design of important and successful HPC systems. However, I realized that HPC is about more than just hardware: it is an ecosystem that includes software, applications, facilities, educators, software developers, scientists, administrators, sponsors, and many other factors. This book is a snapshot of these contemporary HPC ecosystems, which are typically punctuated with a site's flagship system. Broadly speaking, HPC is growing internationally, so I invited contributions from a broad base of organizations including the USA, China, Japan, Russia, Germany, and Switzerland. My excitement about this book grew as I started inviting authors to contribute: everyone said 'yes!' In fact, due to the limitations on hardback publishing, we had to limit the number of chapters that we could include in this edition; however, change in HPC is accelerating, so a second edition of this book may be warranted. As I explain in the introduction, the rate of change in HPC is accelerating"--